Modos de subjetivação e saúde mental : a construção do corpo nos dispositivos CAPS II AD em Vitória da Conquista - Santos, Regiane Lacerda (2015)
This paper aims to analyze the production of discourses that cross and constitute the body within the public mental health policies in Vitória da Conquista city, and the Psychosocial Care Center II - CAPS II and the Psychosocial Care Center Alcohol and other Drugs - CAPS AD used as clipping. The issue revolves around, the following question: how does the production of forms of subjectivity and body in public mental health policy, while bio-political device located? To do this we will have a theoretical discussion from some works of Michel Foucault. From the perspective that the bodies are made up of tangled essay questions linked to situations biopsychosocial, economic and political, in which the discourse produces subjective and objective practices (subjectivity modes) that produce subject and thus bodies. The object-subject adopted in research are the regimes of truth and in what concerns the methodological strategy elect oral history, where the procedures used were the daily narratives, whether in team meeting in therapeutic workshops, in assemblies, etc., as also we lay hold of semi-structured interviews. The categories of analysis, covering the body, adopted are: the body-politics, the body-expert and body-user, therefore, as speeches crossing and constitute the body of the subjects inserted in this policy now have the location of these services while health institutions, and this implies a structure through guidelines and national health policy standards and the prospect that the psychiatric reform is still under construction, thus forms of mental health care can be rethought, redone all day, what evidence the substitute services are part of an ongoing process, and finally, the attempt to prevent a recurrence of mental institutions.